Advances in industrial and labor relations. Vol. 26 - Lewin, David; Gollan, Paul J. (Emerald Publishing Limited, 2021)
Volume 26 of 'Advances in Industrial and Labor Relation's (AILR) contains six new peer-reviewed papers highlighting key aspects of employment relations a variety of disciplinary perspectives. The topics of these papers include a historical analysis of the first trade association of commercial printers, the prospects for free riding in public sector unions following a key U.S. Supreme Court decision, the increasing stratification of college and university faculty, procedural and distributive justice aspects of sexual harassment arbitrations in unionized settings, the effects of third-party neutral sourcing and qualifications on employment ADR practice in large companies, and the measurement of democratic spillover from workplaces to politics. As with prior AILR volumes, the papers in Volume 26 display a variety of quantitative and qualitative research methods. These range from primary research methods such as case studies, survey, interviews and historiography to longitudinal and cross-sectional empirical studies and theory building. Some of the research included in this volume was first presented at the 71th annual meeting of the Labor and Employment Relations Association (LERA) held in Cleveland, Ohio (USA) during June 2019.
Includes index.
Keywords: Industrial relations.; Political Science -- Labor & Industrial Relations.; elektronické knihy; electronic books